2012
DOI: 10.3130/aija.77.995
|View full text |Cite
|
Sign up to set email alerts
|

Actual Situation and Issues of a School-Age Childcare Centre in Japan

Abstract: In this paper, we first address actual situation of a childcare environment. Secondly, childcare environment for different basic conditions, defined by management style, building planning and location, is addressed. Finally, relationship between childcare environment and children's activities are presented, which leads to clarify issues of each basic conditions.The results are as follows. 1) Number of children, management style and building planning of school-age childcare centres were diverse in japan. 2) Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In response to this growing demand, the schoolchild care services, which began in the 1950 s under the management of parents' associations, etc., were institutionalized in 1997 under the Child Welfare Act, and since then, facilities have been rapidly established mainly in elementary schools in Japan. As of 2014, 22 000 facilities have been established nationwide and have achieved certain results 1 . However, according to the National Liaison Council for After‐School Childcare, the number of children on waiting lists is estimated to be about 400 000 [Note 1], and since establishment of facilities has not been keeping pace with the growing demand, many municipalities have responded by increasing or not limiting the capacity of facility in order to expand the quantity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to this growing demand, the schoolchild care services, which began in the 1950 s under the management of parents' associations, etc., were institutionalized in 1997 under the Child Welfare Act, and since then, facilities have been rapidly established mainly in elementary schools in Japan. As of 2014, 22 000 facilities have been established nationwide and have achieved certain results 1 . However, according to the National Liaison Council for After‐School Childcare, the number of children on waiting lists is estimated to be about 400 000 [Note 1], and since establishment of facilities has not been keeping pace with the growing demand, many municipalities have responded by increasing or not limiting the capacity of facility in order to expand the quantity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the supply status of schoolchild care facilities include a study which analyzed the relationship between the basic conditions (management body, type of facility, and location of opening) and the state of activities, and summarized the issues in each condition for fixing childcare environments, based on a nationwide questionnaire survey (235 facilities), 1 as well as a study which showed the actual differences in supply status according to population size, measures taken for resolving issues such as dividing large facilities, and the effect of the formulation of the Guidelines on the institution of municipal guidelines, based on a questionnaire survey of all municipalities (1031 municipalities) 2 . We analyzed the relationship between the regional categories of former municipalities and the types of facilities established throughout the Chugoku and Shikoku Regions, and pointed out the differences in the types of facilities established in urban and depopulated rural areas, as well as the regional disparities in the facility establishment rate and the quality of facilities 3,4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation